Screening and Characterization of Potential Plant Growth-Promoting Endophytes of Wheat (Triticum aestivum) - Awasthi, Shashank; Wadhwa*, Neeraj (CURRENT APPLIED SCIENCE AND TECHNOLOGY, 2023)
Wheat is the principal and most consumed grain in the world. Biotic factors are known to affect the growth of wheat plants and grain yield worldwide. The aim of the present study was to isolate potential plant growth promoting endophytes. In this study, bacterial endophytes from germinating wheat seeds were isolated, characterized, and screened in vitro for PGP traits and then checked for their effects on germination and production of indole acetic acid (IAA), ACC deaminase activity, siderophore production, phosphate solubilization, HCN production, extracellular enzyme production and biocontrol potential. High potential PGPRs were identified by 16 s rRNA sequencing and these strains are Enterobacter asburiae, Bacillus licheniformis, Achromobacter mucicolens, and Pseudomonas fulva. Antagonistic activity results showed that B. licheniformis, and A. mucicolens could reduce the growth of the fungal phytopathogens. Alternaria alternata and Fusarium sp. also produced high levels of indole acetic acid (IAA) with a range of 27.8±0.30 µg/mL, 31.2±0.36, 21±0.20, respectively. Seed germination and development studies showed that superior increase of root and shoot length and weight were observed when compared with uninoculated control plants. The study revealed that the isolated endophytes could be used as plant growth promotion for better plant yield. Keywords: endophytes; PGPR traits; antagonistic bacteria; Tritium aestivum; 16s rRNA *Corresponding author: E-mail: neeraj.wadhwa@jiit.ac.in